The effect of exercise on leg vascular conductance and oxygen uptake kinetics, and endothelial and inflammatory function in women with type 2 diabetes - Kiely, Catherine (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Individuals with type 2 diabetes (T2DM) show a reduced maximal oxygen uptake (VO2 peak) in comparison to age, BMI, and activity matched non-diabetic (ND) controls. In addition, the dynamic responses of VO2 (VO2 kinetics) and leg vascular conductance (LVC) are slowed in combined groups of pre and postmenopausal women with T2DM. As yet, VO2 and LVC kinetic responses have not been investigated in postmenopausal women with T2DM. The mechanisms underpinning the impaired VO2 kinetic responses have not been well elucidated but it is thought that central factors affecting cardiac function and/or peripheral factors affecting oxygen delivery and oxygen extraction may be responsible. Exercise training has been shown to have beneficial effects on VO2 peak and VO2 kinetics in premenopausal women and in a combined group of men and women with T2DM, but again, no studies have looked at the effect of exercise training on these parameters in postmenopausal women and furthermore, the mechanistic bases for this exercise improvements are not known.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin